(untitled) (Annals of Medical Research, 2021)
Aim: The virtual innovation is offered the new opportunities rather than teaching didactic content in pediatric nursing. The aim of the study was to examine the effect of the VBAP simulation on the emotional development with students in pediatric nursing education.Material and Methods: This study utilized an experimental design with a pre- and post-test with 52 nursing students (24 for experimental and 28 for control groups). The Virtual Baby Adopter Program (VBAP) simulation used as an intervention on own mobile phone for experiment groups. The experiment group used the VBAP simulation program daily belonging to proper the plan for baby feeding and care applications for 80 days. Results: There was significant between experiment and control groups’ participants living of children levels in post-test scores. The experiment group’ level of the bonding is a strong and they felt positive emotion as loving, joyful, and protective. The experiment group’ level of the caregiver strain is a low. Conclusions: It is observed that the virtual program in pediatric education is a way to effect that developed for participants liking of children as a strong emotion of bonding and low caregiver strain.